Caracterização tecnológica de Enterococcus faecium isolados de queijos artesanais - Paula, Priscila Lima Magarotto de (2019)
The search for bacteria with beneficial properties to health, nutritional quality, as well as food preservation has been the focus of intense research in the area of food. The isolation and characterization of our species are useful for obtaining isolates with different technological and functional characteristics. From this perspective, this study evaluated the technological profile of six Enterococcus faecium (EFM 55, EFM 67, EFM 9A, EFM 16A, EFM19A and EFM 44) isolated from cheese. The enzymatic activities of proteolysis and lipolysis at different incubation times were evaluated. The enzymatic activities of proteolysis and lipolysis at different incubation times were evaluated. Beta-galactosidase enzyme testing, acidification capacity, antagonistic activity against food pathogens, antimicrobial susceptibility and continuous use medications were also performed. All isolates showed proteolytic activity from 48 hours at 20ºC. Lipolytic activity and beta-galactosidase were not detected. Isolate EFM 44 showed intermediate resistance to ciprofloxacin and erythromycin, while EFM 55 were resistant just to erythromycin, the remaining isolates were sensitive to all antimicrobials tested. The EFM 44 showed increase in pH and titratable acidity at 20ºC over 48 hours. The EFM 9A and 19A showed no resistance to dipyrone, while the others were resistant to all evaluated drugs. The EFM 9A isolate showed inhibition against all tested pathogens, and the others were effective in controlling E. coli. We conclude that the Enterococcus faecium isolates studied presented technological profile for application in fermented dairy products.